2016
DOI: 10.1186/s40064-016-3156-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of ligninolytic enzymes of white rot fungi (Pleurotus spp.) grown with azo dyes

Abstract: BackgroundTotal three Pleurotus species (P. ostreatus, P. sapidus, P. florida) was compared for ligninolytic enzyme production grown with Coralene Golden Yellow, Coralene Navy Blue and Coralene Dark Red azo dyes in liquid medium under shaking condition.ResultsThe biodegradation competency varied from species to species and it was found that P. ostreatus, P. sapidus and P. florida to 20 ppm dye concentration shows 88, 92 and 98 % decolorization, respectively for all three dyes. Production pattern of laccase, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 52 publications
0
22
0
4
Order By: Relevance
“…This does not represent the lowest potential bioremediator since this isolate presented steady growth with less reduction in growth as a result of the increase in the dye concentration and the discoloration, indicating degradation of the chemical compound according to Kundjadia et al (2016). Isolates DF39, EF58, FUS and PS have the potential to degrade the dye, even with a smaller diameter for the mycelial growth, as observed with the DF39 isolate in the solid medium.…”
Section: Mycelial Growth and Discoloration Of Methylene Blue In The Smentioning
confidence: 96%
See 3 more Smart Citations
“…This does not represent the lowest potential bioremediator since this isolate presented steady growth with less reduction in growth as a result of the increase in the dye concentration and the discoloration, indicating degradation of the chemical compound according to Kundjadia et al (2016). Isolates DF39, EF58, FUS and PS have the potential to degrade the dye, even with a smaller diameter for the mycelial growth, as observed with the DF39 isolate in the solid medium.…”
Section: Mycelial Growth and Discoloration Of Methylene Blue In The Smentioning
confidence: 96%
“…E Abo-State et al (2011) also associate the process of discoloration of the culture medium with methylene blue by the action of the laccase enzyme, which belongs to peroxidase and is commonly synthesized by white rot fungi. The degradation of dyes by fungi, such as Pleurotus ostreatus, P. Florida, and P. sapidus, was quantified by Kundjadia et al (2016), who observed the discoloration of 88 to 98% of the dye. In this present study, it was not possible to quantify the percentage of degradation of the dye in the solid medium, although discoloration of the culture medium was observed with isolates DF39, EF58, FUS, and PS, indicating the degradation of the dye.…”
Section: Mycelial Growth and Discoloration Of Methylene Blue In The Smentioning
confidence: 99%
See 2 more Smart Citations
“…El decrecimiento en la absorción del colorante, después de ser sometido a la actividad enzimática del microorganismo, indica que la decoloración del colorante fue debido a la degradación del colorante [13], [14]. Pero, debido a las aminas generadas por el rompimiento del enlace azo, el pH de las aguas residuales aumenta [15], lo que limita la supervivencia de microorganismos en estos cuerpos acuosos.…”
Section: Abstract the Presence Of Colored Wastewater Prevents The Peunclassified